Evaluation of the Implementation of the M-Passport Application Policy at Kantor Imigrasi Kelas II TPI Cilegon - Paulana, Tina; Agustino, Leo; Cadith, Juliannes (Indonesian Journal of Social Science Research, 2026)
Public services in Indonesia are always related to the governance of government agencies, both central and regional, as well as state-owned enterprises, aimed at facilitating the fulfillment of people's rights as citizens. In its services, Direktorat Jenderal Imigrasi has taken a policy step to apply for passports through the M-Paspor application, which has been implemented starting in 2022. Kantor Imigrasi Kelas II TPI Cilegon is one of three Immigration Offices located in Banten Province. Based on the results of the SPBE evaluation in the Regional Government in Banten, Cilegon City received an index of 2.30, with a sufficient predicate. This study aims to evaluate the use of the M-Paspor application in order to accelerate passport issuance services. The CIPP evaluation model is used to evaluate the overall policy by considering the context, input, process, and product that can be used as comprehensive information for future policy improvement and development. The research method used is descriptive with a qualitative approach. The descriptive analysis obtained indicates that the use of the M-Paspor application has been running well but can be further improved to achieve fair and standardized public services.